Genetic characterization of cashmere goat (Capra hircus) populations in Mongolia - Baldan, Sergelen; Sölkner, Johann; Gebre, Kahsa Tadel; Mészáros, Gábor; Crooijmans, Richard; Periasamy, Kathiravan; Pichler, Rudolf; Manaljav, Bayarjargal; Baatar, Narantuya; Purevdorj, Myagmarsuren (Frontiers in Genetics, 2024)
Characterization studies of the phenotypic and genetic diversity of Mongolian goats are limited, despite several goat breeds being registered in the country. This study aimed to evaluate the phenotypic and genetic diversity of 14 cashmere goat populations in Mongolia, consisting largely of identified goat breeds. Body weight, cashmere quality, and coat color were the phenotypic traits considered in this study. A linear model was used to fit body weight and cashmere traits, and least squares means (LSMs) were estimated for the region and location classes. Genetic diversity and structure were assessed using a goat 50K SNP array. The studied populations exhibited greater phenotypic diversity at the regional level. A very small overall differentiation index (Fst: 0.017) was revealed by Wright's Fst and a very small overall inbreeding index (FROH1: 0.019) was revealed based on runs of homozygosity. Genetic clustering of populations by principal components showed large variances for the two goat populations of the Russian admixture (Gobi Gurvan Saikhan and Uuliin Bor), and smaller but differentiated clusters for the remaining populations. Similar results were observed in the admixture analysis, which identified populations with the highest (Govi Gurvan Saikhan and Uuliin Bor) and lowest (Tsagaan Ovoo Khar) exotic admixtures. A genome-wide association study (GWAS) of body weight and cashmere traits identified a few significant variants on chromosomes 2, 4, 5, 9, and 15, with the strongest variant for cashmere yield on chromosome 4. The GWAS on coat color yielded nine significant variants, with the strongest variants located on chromosomes 6, 13, and 18 and potential associations with KIT, ASIP, and MC1R genes. These signals were also found in other studies on coat color and patterns in goats. Mongolian cashmere goats showed relatively low genetic differentiation and low inbreeding levels, possibly caused by the traditional pastoral livestock management system and the practice of trading breeding bucks across provinces, along with a recent increase in the goat population. Further investigation of cashmere traits using larger samples and alternative methods may help identify the genes or genomic regions underlying cashmere quality in goats.